Role and Function of A2A and A3 Adenosine Receptors in Patients with Ankylosing Spondylitis, Psoriatic Arthritis and Rheumatoid Arthritis - Ravani, Annalisa; Vincenzi, Fabrizio; Bortoluzzi, Alessandra; Padovan, Melissa; Pasquini, Silvia; Gessi, Stefania; Merighi, Stefania; Borea, Pier; Govoni, Marcello; Varani, Katia (International journal of molecular sciences, 2017)
Rheumatoid arthritis (RA), ankylosing spondylitis (AS) and psoriatic arthritis (PsA) are chronic inflammatory rheumatic diseases that affect joints, causing debilitating pain and disability. Adenosine receptors (ARs) play a key role in the mechanism of inflammation, and the activation of A2A and A3AR subtypes is often associated with a reduction of the inflammatory status. The aim of this study was to investigate the involvement of ARs in patients suffering from early-RA (ERA), RA, AS and PsA. Messenger RNA (mRNA) analysis and saturation binding experiments indicated an upregulation of A2A and A3ARs in lymphocytes obtained from patients when compared with healthy subjects. A2A and A3AR agonists inhibited nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) activation and reduced inflammatory cytokines release, such as tumor necrosis factor-α (TNF-α), interleukin (IL)-1β and IL-6. Moreover, A2A and A3AR activation mediated a reduction of metalloproteinases (MMP)-1 and MMP-3. The effect of the agonists was abrogated by selective antagonists demonstrating the direct involvement of these receptor subtypes. Taken together, these data confirmed the involvement of ARs in chronic autoimmune rheumatic diseases highlighting the possibility to exploit A2A and A3ARs as therapeutic targets, with the aim to limit the inflammatory responses usually associated with RA, AS and PsA.